A Study of Brain and Serum Brain-Derived Neurotrophic Factor Protein in Wistar and Wistar-Kyoto Rat Strains after Electroconvulsive Stimulus - Kyeremanteng, C.; James, J.; MacKay, J.; Merali, Z. (Pharmacopsychiatry, 2012)
Serum brain-derived neurotrophic factor (BDNF) protein has been related to depression and less consistently to its treatments in human studies. However, animal studies have failed to demonstrate a clear link between BDNF protein in serum and brain tissue.Serum and brain tissue levels of BDNF protein were measured with ELISA in the Wistar-Kyoto (WKY) and Wistar strains at 1 and 7 days after 5 daily electroconvulsive stimulus sessions or sham treatments.The WKY strain showed lower baseline serum BDNF protein relative to Wistar controls. After 5 electroconvulsive stimuli, BDNF protein density was significantly increased in hippocampus and cortical regions, but not in the cerebellum or in serum. A clear correlation between brain and serum BDNF was not observed in either strain or treatment group.Despite lower baseline serum BDNF protein in the WKY strain, a lack of change in serum BDNF after electroconvulsive stimulus and a lack of correlation between brain and serum BDNF protein calls into question the relevance of serum BDNF as a measure of depression and treatment response.
Keywords: animal models; depression; electroconvulsive therapy (ECT)